2019
DOI: 10.5535/arm.2019.43.6.625
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Language Function and Recovery-Related Prognostic Factors in First-Ever Left Hemispheric Ischemic Stroke

Abstract: Objective To investigate longitudinal changes in language function in left-hemispheric ischemic stroke patients as well as factors that influence language recovery until 1 year after stroke onset. Methods We analyzed data from 235 patients with first-ever left-hemispheric ischemic stroke. All patients completed the Korean version of the Frenchay Aphasia Screening Test (K-FAST) at 7 days (T1), 3 months (T2), 6 months (T3), and 1 year (T4) after stroke onset. Repeated measures analysis of variance (ANOVA) was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Regarding lesion location, some studies suggest that lesions involving the left STG (superior temporal gyrus) and Wernicke's area are associated with poor aphasia improvement [ 70 ]. With regard to lesion magnitude, even though large left hemisphere lesions are typically associated with poorer recovery [ 71 ], in a recent study, patients with larger stroke volumes showed greater aphasia improvements regardless of the involvement of the language areas [ 72 ]. This could explain the findings from the current study in which the only participant who showed statistically significant improvements had diffuse and large brain lesions in the left hemisphere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding lesion location, some studies suggest that lesions involving the left STG (superior temporal gyrus) and Wernicke's area are associated with poor aphasia improvement [ 70 ]. With regard to lesion magnitude, even though large left hemisphere lesions are typically associated with poorer recovery [ 71 ], in a recent study, patients with larger stroke volumes showed greater aphasia improvements regardless of the involvement of the language areas [ 72 ]. This could explain the findings from the current study in which the only participant who showed statistically significant improvements had diffuse and large brain lesions in the left hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the role of BDNF (brain-derived neurotrophic factor) variants on language recovery poststroke is emerging, and several studies have demonstrated that it influences recovery [ 75 , 76 ]. Also, through univariate analysis, it has been shown that total lean body mass—not adipose tissue—may be a positive factor for predicting aphasia improvement [ 72 ]. Lastly, evidence in relation to the impact of sex [ 77 ], handedness, and educational background [ 78 ] on language recovery is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…19 An individual's level of schooling is known to affect both recovery and language performance poststroke. 37,38 Individuals with low levels of schooling employ simpler grammar structures and use more oral than written language, and they do not engage as much in social reading and writing activities. 38,39 The results obtained herein may be associated with the level of schooling of the sample; indeed, in Brazil, much of the population suffers from limited access to formal education.…”
Section: Discussionmentioning
confidence: 99%
“…Even though it is reasonable to assume that larger lesions may affect language network hubs and consequently confer a greater negative impact on language recovery, findings regarding lesion magnitude are controversial. While it has been shown that larger lesions are associated with poorer recovery e.g., [ 120 ], there is evidence that this is not always the case [ 121 ]. Considering the existing evidence connecting the location and size of lesions, it is important to understand their combined impact on aphasia recovery.…”
Section: Can We Predict Which Pwa Will Respond To Treatment?mentioning
confidence: 99%